Indians of the Southwest - Liptak, Karen (New York : Facts on File, 1991)
Examines the history, culture, changing fortunes, and current situation of the various Indian peoples of the Southwest
Includes index
Keywords: Indians of North America -- Southwest, New -- Juvenile literature